The role of performance management system in shaping psychological contract: a case study approach - Newaz, Mohammad Tanvi (© 2012 SPIRI (Society for Promoting International Research and Innovation), 2016)
This article was published in International Journal of Business and Management Tomorrow [© 2012 SPIRI (Society for Promoting International Research and Innovation) ] and the definite version is available at : https://www.researchgate.net/publication/265226576_The_Role_of_Performance_Management_System_In_Shaping_Psychological_Contract_A_Case_Study_Approach